KEBUTUHAN SISWA DAN PERMINTAAN KURIKULUM BAHASA INGGRIS: PROGRAM PAKET C DI PKBM - Zuharty Zuharty; Ifan Iskandar; Eko Budiarto (Jurnal Ilmiah Visi, 2010)
This study aims at finding out how far the English Package C curriculum meets the Package C learnerS needs Of English to pass the national examination (UN) and identify whether the learners* needs in learning listening, speaking, reading, and writing, skills are acommodated by he curriculum. The subjects Of the Study were 27 learners of Package C Program, consisting of 7 Terampil learners and 20 Mahir learners at the Community Learning Center (PKBM) 33 Malaka, East Jakarta. Questionnaires and interviews were conducted to get the data. The study revealed that the curriculum contents, though not complete, could accommodate most of the Package C learners' needs to learn reading, writing, listening and speaking skills although the tutor did not teach all the four skills. It was also found that the learners had some expectations: they needed more time to practice the four language skills in class, and sufficient teaching aids to SUDDort the Jearning-teaching process so that the learning would be more efficient.